2011
DOI: 10.1001/archophthalmol.2010.350
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab in Refractory Neovascular Glaucoma

Abstract: To examine the efficacy of intravitreal bevacizumab for pain relief in eyes with refractory neovascular glaucoma.Methods: In this prospective case series, 52 eyes with neovascular glaucoma were administered intravitreal bevacizumab, 1.25 mg, and monitored for 6 months. The primary outcome measure was change in subjective pain score. Intraocular pressure and iris neovascularization were evaluated at each visit. Surgical intervention for control of intraocular pressure was performed according to clinical need. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…23 We have observed by slit lamp examination and by iris angiography that iris neovascularization is completely regressed within 3 days of intravitreal bevacizumab injection. However, bevacizumab, although rapidly-acting, induces temporary antiangiogenic effects with recurrence of neovascularization, 28,33 due to its short duration of action. 34,35 On the other hand, the effects of PRP appear to be more long lasting, suggesting that eyes with NVG can benefit from both the early-onset Figure 1 (a) Kaplan-Meier Survival Analysis of NVG Eyes Receiving GDIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 We have observed by slit lamp examination and by iris angiography that iris neovascularization is completely regressed within 3 days of intravitreal bevacizumab injection. However, bevacizumab, although rapidly-acting, induces temporary antiangiogenic effects with recurrence of neovascularization, 28,33 due to its short duration of action. 34,35 On the other hand, the effects of PRP appear to be more long lasting, suggesting that eyes with NVG can benefit from both the early-onset Figure 1 (a) Kaplan-Meier Survival Analysis of NVG Eyes Receiving GDIs.…”
Section: Discussionmentioning
confidence: 99%
“…Case series and retrospective studies have reported only short-term reduction in neovascularization, inflammation and IOP in eyes receiving anti-VEGF agents. 24,28,30,33,36,[42][43][44][45] A systematic review of literature in 2013 concluded that no compelling evidence exists from which reliable conclusions could be drawn comparing the effects of anti-VEGF agents either alone or as an adjunctive modality to other forms of treatment but no anti-VEGF agents in NVG. 46 The review identified two RCTs evaluating intravitreal bevacizumab injection in NVG.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In a previous paper published by our group and entitled 'Outcomes of treatment of neovascular glaucoma with intravitreal bevacizumab', Kaplan-Meier analysis in Figure 3 10 revealed a linear increase in the cumulative proportion of NVG eyes receiving a second IVB injection with time. The reason for repeated injections was most likely recurrent or persistent NVI and/or neovascularization of anterior chamber angle.…”
mentioning
confidence: 87%
“…12 Additional intravitreal anti-VEGF has also been shown to be a useful adjunct in producing rapid pain relief in refractory neovascular glaucoma. 13 Long-term outcomes and the prognosis of eyes treated with the latest approaches in the management of neovascular glaucoma are lacking from recent literature. However, the addition of intravitreal anti-VEGF has revolutionised the treatment of neovascular glaucoma, and in combination with early detection, thorough pan-retinal photocoagulation and safe surgical intervention should result in long-lasting maintenance of visual functional and acceptable IOP control.…”
Section: Table 1: Clinical Experiencesmentioning
confidence: 99%